Method for preparing reduced graphene oxide-zirconium oxide wave-absorbing composite material by hydrothermal technology
Preparation of reduced graphene oxide @zirconia wave absorbing composite materials through hydrothermal technology has solved the problems of poor powder dispersion and different crystallinity in the existing technology, and achieved efficient preparation of composite materials and excellent absorption performance, meeting the needs of high-performance wave absorbing materials.
Patent Information
- Application Number
- CN202510011576.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-04
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when preparing reduced graphene oxide @zirconia wave absorbing composite materials, there are problems such as poor powder dispersion, different crystallinity, and possible escape of gases and organic matters during drying, which affects the performance of the material.
Reduced graphene oxide @zirconia wave absorbing composite material is prepared by hydrothermal technology. By thoroughly mixing Zr(NO3)4·5H2O and RGO in deionized water, adjusting the pH value, conducting hydrothermal reaction, and then washing, drying and calcining to obtain a composite material with excellent wave absorbing performance.
It realizes efficient preparation of composite materials, has excellent electromagnetic wave absorption performance, significant synergistic effect, simple process, environmentally friendly and economical, and meets the needs of high-performance wave absorbing materials.
Smart Images

Figure CN119706927A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a method for preparing a reduced graphene oxide@zirconium oxide wave-absorbing composite material by using a hydrothermal technology. Background Art
[0002] With the rapid development of information technology, electromagnetic interference pollution has become a major problem in the military field. Absorbing materials, as a material that can effectively absorb and weaken electromagnetic waves, have received great attention from the military scientific research community. They have broad application prospects in many fields such as military stealth materials, biomedical materials, radiation-proof clothing and electromagnetic shielding. With the popularization of high-tech reconnaissance and precision guidance technology, higher requirements are placed on the stealth capabilities of weapons and equipment. It is necessary to maintain stable absorbing performance in extreme environments. The research and development of high-performance absorbing materials has become the focus of current research.
[0003] Reduced graphene oxide (RGO) is a material with excellent microwave absorption properties and has attracted widespread attention in the field of electromagnetic wave absorption. RGO has the advantages of ultra-wideband absorption, light weight, compressibility, high temperature resistance, and high absorption intensity. The microwave absorption performance of RGO is mainly attributed to its unique two-dimensional structure and excellent electrical properties. RGO shows enhanced microwave absorption compared to graphene and can be combined with other materials to form composite materials with stronger microwave absorption performance.
[0004] Zirconia (ZrO2) is a material with high melting temperature, strong chemical stability, high strength, high hardness, and excellent wear resistance. It is widely used in refractory materials, high-temperature absorbing coatings, absorbing materials, etc. The composite of RGO and ZrO2 can significantly improve the tensile strength, hardness and wear resistance of the composite material, enhance the chemical stability of the composite material, and significantly enhance the absorbing performance.
[0005] The preparation methods of the composite of the two materials include coprecipitation method, sol-gel method, etc. However, the preparation methods of the above-mentioned prior arts have the following problems:
[0006] 1) In the co-precipitation method, the powder dispersion will be poor, affecting the material properties. The reaction rate during the co-precipitation process may be difficult to accurately control, resulting in different crystallinity of the material;
[0007] 2) In the sol-gel method, there are a large number of micropores in the gel, and gas and organic matter may escape during the drying process, causing shrinkage.
[0008] In view of the problems existing in the above-mentioned prior art, the present invention provides a method for preparing a reduced graphene oxide @ zirconium oxide absorbing composite material by hydrothermal technology. The method uses reduced graphene oxide as a base material and zirconium nitrate as a zirconium source, and finally obtains a reduced graphene oxide @ zirconium oxide composite material with excellent absorbing performance through hydrothermal and other technologies.
[0009] The invention utilizes the hydrothermal method to prepare a lightweight, high-performance wave-absorbing nanocomposite material, which has important academic and application values. Summary of the invention
[0010] The purpose of the present invention is to provide a method for preparing a reduced graphene oxide@zirconium oxide wave absorbing composite material by using a hydrothermal technology.
[0011] In the present invention, a hydrothermal method is used to prepare a two-material composite. The hydrothermal reaction can change the state of the crystal by changing factors such as the reaction temperature and the hydrothermal time, thereby obtaining different morphologies and properties. The hydrothermal method is simple and easy to operate. It only needs to set parameters such as the reaction temperature and time to carry out the reaction, saving manpower and time costs.
[0012] The obtained reduced graphene oxide @ zirconium oxide composite material has the advantages of light weight, wide effective frequency band range, good wave absorbing performance and simple preparation method.
[0013] To achieve the above object, the present invention is implemented by the following technical solutions:
[0014] A method for preparing a reduced graphene oxide@zirconia microwave absorbing composite material by hydrothermal technology, comprising the following preparation steps:
[0015] S1 was fully fused with Zr(NO3)4·5H2O and RGO in deionized water, and the mixed solution was magnetically stirred;
[0016] S2 added NH3·H2O to adjust the pH value;
[0017] S3 reacts the mixed solution in a stainless steel high-pressure reactor;
[0018] S4 washing the product;
[0019] S5 dries the product;
[0020] After S6 drying, the obtained product is calcined in an atmosphere furnace.
[0021] As a further improvement of this solution, the detailed steps of S1 are:
[0022] RGO and Zr(NO3)4·5H2O were taken according to the molar mass ratio of 1:0.1, 1:0.2, and 1:0.3, and mixed with 40 mL of deionized water. The mixed solution was ultrasonically stirred for 1 hour, and the dispersed solution was magnetically stirred for 0.5 hour to uniformly disperse RGO and Zr(NO3)4·5H2O in the solution.
[0023] As a further improvement of this scheme, the detailed steps of S2 are: taking 0.5 mL of NH3·H2O, adding NH3·H2O dropwise to the reaction mixture, and adjusting the pH value to 9.
[0024] As a further improvement of this scheme, the detailed steps of S3 are: transferring the dissolved solution into a 100 mL stainless steel high-pressure reactor, the reaction temperature is 150° C.-210° C., and the reaction time is 1-5 hours.
[0025] As a further improvement of this solution, the detailed steps of S4 are: washing the obtained product with deionized water for a certain number of times to make the pH value reach a neutral value.
[0026] As a further improvement of this solution, the detailed steps of S5 are: after washing, drying in a vacuum oven at 60° C. for 24 hours.
[0027] As a further improvement of the present solution, the detailed steps of S6 are: placing the product in an atmosphere furnace for calcining at 400° C. for 3 hours to obtain the final product.
[0028] The method for preparing reduced graphene oxide@zirconia absorbing composite material by hydrothermal technology of the present invention has the following beneficial effects:
[0029] 1) The present invention has excellent electromagnetic wave absorption performance and significant synergistic effect:
[0030] The reduced graphene oxide @ zirconium oxide (RGO@ZrO2) composite material prepared by the hydrothermal technology of the present invention exhibits excellent microwave absorption performance due to its unique microstructure and physical and chemical properties. The high conductivity of reduced graphene oxide and the high dielectric constant of zirconium oxide form a significant synergistic effect, which enables the material to have a high electromagnetic wave absorption efficiency in a wide frequency range. At the same time, zirconium oxide particles are evenly dispersed on the surface of reduced graphene oxide, effectively reducing interface reflection loss and improving microwave absorption capacity, thereby meeting the high performance requirements of microwave absorbing materials;
[0031] 2) The present invention optimizes the process to achieve high stability and consistency:
[0032] The present invention ensures that the prepared composite material has high structural stability and good repeatability by optimizing the molar mass ratio, hydrothermal temperature, and hydrothermal time parameters. Specifically, by precisely adjusting the pH value to 9, the growth process of zirconium oxide crystals is effectively controlled, significantly improving the structural integrity and wave absorption performance of the composite material; the atmosphere furnace calcination technology is used to further improve the crystal phase purity and bonding strength of zirconium oxide, thereby improving the durability and long-term performance of the material. The above process design not only simplifies the preparation process, but also makes the product performance more uniform and reliable;
[0033] 3) The preparation process of the present invention is green and environmentally friendly, and has strong economic applicability:
[0034] The present invention adopts a green preparation process, uses deionized water as solvent, and uses conventional reagents (Zr(NO3)4·5H2O and NH3·H3O), avoiding the use of complex toxic organic solvents and meeting environmental protection requirements. The preparation process has low energy consumption and simple operation, which significantly reduces production costs. At the same time, the material properties are further optimized through vacuum drying and atmosphere furnace calcination processes. The RGO@ZrO2 composite material finally prepared has excellent performance and broad industrial application prospects, providing technical support for the low-cost and efficient preparation of absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The SEM images of RGO@ZrO2 with different hydrothermal ratios of the present invention;
[0036] Figure 1 (a) is the SEM image of RGO@ZrO2 with a ratio of 1:0.1 in comparative example 1;
[0037] Figure 1 (b) is the SEM image of RGO@ZrO2 with a ratio of 1:0.2 in Example 1;
[0038] Figure 1 (c) is the SEM image of RGO@ZrO2 with a ratio of 1:0.3 in comparative example 3;
[0039] Figure 2 Hydrothermal XRD patterns of RGO@ZrO2 at different ratios;
[0040] Figure 3 Hydrothermal dielectric constant diagram of RGO@ZrO2 under different ratios;
[0041] Figure 4 Impedance matching diagram of RGO@ZrO2 hydrothermal decay constant under different ratios;
[0042] Figure 4 (a) is the water-thermal impedance matching diagram of RGO@ZrO2;
[0043] Figure 4 (b) is the hydrothermal decay constant diagram of RGO@ZrO2;
[0044] Figure 5 RL diagrams of hydrothermal RGO@ZrO2 with different ratios;
[0045] (a) is the RL diagram of RGO@ZrO2 with a ratio of 1:0.1 in comparative example 1;
[0046] (b) is the RL diagram of RGO@ZrO2 with a ratio of 1:0.2 in Example 1;
[0047] (c) is the RL diagram of RGO@ZrO2 with a ratio of 1:0.3 in comparative example 2;
[0048] Figure 6 RL diagram of RGO@ZrO2 hydrothermal with different hydrothermal times;
[0049] (a) is the RL diagram of RGO@ZrO2 with hydrothermal time of 1 h in comparative example 3;
[0050] (b) is the RL diagram of RGO@ZrO2 in comparative example 4 with a hydrothermal time of 5 h;
[0051] Figure 7 RL diagrams of RGO@ZrO2 hydrothermal at different hydrothermal temperatures;
[0052] (a) Comparative Example 5 is the RL diagram of RGO@ZrO2 with a hydrothermal temperature of 150 °C;
[0053] (b) Comparative Example 6 is the RL diagram of RGO@ZrO2 with a hydrothermal temperature of 210 °C;
[0054] Figure 8 RL diagram of graphene@alumina prepared by atomic layer deposition technology for comparative example 7. DETAILED DESCRIPTION
[0055] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described below in conjunction with embodiments and drawings:
[0056] Example 1
[0057] A method for preparing a reduced graphene oxide@zirconia absorbing composite material using a hydrothermal technique is carried out according to the following steps:
[0058] S1 Take RGO and Zr(NO3)4·5H2O with a molar mass ratio of 1:0.2, mix them with 40mL of deionized water, stir the mixed solution ultrasonically for 1 hour, and stir the dispersed solution magnetically for 0.5 hour to make RGO and Zr(NO3)4·5H2O uniformly dispersed in the solution.
[0059] S2 Take a certain amount of NH3·H2O and add NH3·H2O dropwise to the reaction mixture to adjust the pH value to 9.
[0060] S3 transferred the dissolved solution into a 100 mL stainless steel high-pressure reactor, the reaction temperature was 180°C, and the reaction time was 3 hours.
[0061] S4: washing the obtained product with deionized water for a certain number of times to make the pH value reach a neutral value.
[0062] After washing, S5 was dried in a vacuum oven at 60 °C for 24 h.
[0063] S6 puts the product into an atmosphere furnace for calcination at 400°C for 3 hours, and performs a performance test on the final product.
[0064] Proportional comparison experiment:
[0065] Comparative Example 1
[0066] A method for preparing a reduced graphene oxide@zirconia absorbing composite material using a hydrothermal technique is carried out according to the following steps:
[0067] S1 Take RGO and Zr(NO3)4·5H2O with a molar mass ratio of 1:0.1, mix them with 40mL of deionized water, stir the mixed solution ultrasonically for 1 hour, and stir the dispersed solution magnetically for 0.5 hour to make RGO and Zr(NO3)4·5H2O uniformly dispersed in the solution.
[0068] S2 Take a certain amount of NH3·H2O and add NH3·H2O dropwise to the reaction mixture to adjust the pH value to 9.
[0069] S3 transferred the dissolved solution into a 100 mL stainless steel high-pressure reactor, the reaction temperature was 180°C, and the reaction time was 3 hours.
[0070] S4: washing the obtained product with deionized water for a certain number of times to make the pH value reach a neutral value.
[0071] After washing, S5 was dried in a vacuum oven at 60 °C for 24 h.
[0072] S6 puts the product into an atmosphere furnace for calcination at 400°C for 3 hours, and performs a performance test on the final product.
[0073] Comparative Example 2
[0074] A method for preparing a reduced graphene oxide@zirconia absorbing composite material using a hydrothermal technique is carried out according to the following steps:
[0075] S1 Take RGO and Zr(NO3)4·5H2O with a molar mass ratio of 1:0.3, mix them with 40mL of deionized water, ultrasonically stir the mixed solution for 1 hour, and magnetically stir the dispersed solution for 0.5 hour to make RGO and Zr(NO3)4·5H2O uniformly dispersed in the solution.
[0076] S2 Take a certain amount of NH3·H2O and add NH3·H2O dropwise to the reaction mixture to adjust the pH value to 9.
[0077] S3 transferred the dissolved solution into a 100 mL stainless steel high-pressure reactor, the reaction temperature was 180°C, and the reaction time was 3 hours.
[0078] S4: washing the obtained product with deionized water for a certain number of times to make the pH value reach a neutral value.
[0079] After washing, S5 was dried in a vacuum oven at 60 °C for 24 h.
[0080] S6 puts the product into an atmosphere furnace for calcination at 400°C for 3 hours, and performs a performance test on the final product.
[0081] Proportional principle analysis:
[0082] By comparing the examples with the comparative examples, when the molar mass ratio of RGO to Zr(NO3)4·5H2O is 1:0.2, zirconium oxide can form a uniform and dense dispersion on the surface of RGO, thereby maximizing the synergistic effect between the two materials. Too low a ratio (1:0.1) may lead to insufficient distribution of zirconium oxide, and the dielectric loss capacity of the composite material is weak; while too high a ratio (1:0.3) may lead to agglomeration of zirconium oxide, which reduces the electromagnetic wave absorption efficiency of the composite material.
[0083] Hydrothermal time comparison experiment:
[0084] Comparative Example 3
[0085] A method for preparing a reduced graphene oxide@zirconia absorbing composite material using a hydrothermal technique is carried out according to the following steps:
[0086] S1 Take RGO and Zr(NO3)4·5H2O with a molar mass ratio of 1:0.2, mix them with 40mL of deionized water, stir the mixed solution ultrasonically for 1 hour, and stir the dispersed solution magnetically for 0.5 hour to make RGO and Zr(NO3)4·5H2O uniformly dispersed in the solution.
[0087] S2 Take a certain amount of NH3·H2O and add NH3·H2O dropwise to the reaction mixture to adjust the pH value to 9.
[0088] S3 transferred the dissolved solution into a 100 mL stainless steel autoclave, the reaction temperature was 180 °C, and the reaction time was 1 hour.
[0089] S4: washing the obtained product with deionized water for a certain number of times to make the pH value reach a neutral value.
[0090] After washing, S5 was dried in a vacuum oven at 60 °C for 24 h.
[0091] S6 puts the product into an atmosphere furnace for calcination at 400°C for 3 hours, and performs a performance test on the final product.
[0092] Comparative Example 4
[0093] A method for preparing a reduced graphene oxide@zirconia absorbing composite material using a hydrothermal technique is carried out according to the following steps:
[0094] S1 Take RGO and Zr(NO3)4·5H2O with a molar mass ratio of 1:0.2, mix them with 40mL of deionized water, stir the mixed solution ultrasonically for 1 hour, and stir the dispersed solution magnetically for 0.5 hour to make RGO and Zr(NO3)4·5H2O uniformly dispersed in the solution.
[0095] S2 Take a certain amount of NH3·H2O and add NH3·H2O dropwise to the reaction mixture to adjust the pH value to 9.
[0096] S3 transferred the dissolved solution into a 100 mL stainless steel high-pressure reactor, the reaction temperature was 180°C, and the reaction time was 5 hours.
[0097] S4: washing the obtained product with deionized water for a certain number of times to make the pH value reach a neutral value.
[0098] After washing, S5 was dried in a vacuum oven at 60 °C for 24 h.
[0099] S6 puts the product into an atmosphere furnace for calcination at 400°C for 3 hours, and performs a performance test on the final product.
[0100] Analysis of hydrothermal time principle:
[0101] The hydrothermal time has a significant effect on the wave absorption performance of reduced graphene oxide composite zirconium oxide (RGO@ZrO2) materials. A shorter hydrothermal time (1 hour) leads to incomplete growth of zirconium oxide crystals, small and uneven distribution of particles, and insufficient reduction of RGO, resulting in poor electromagnetic wave absorption of the composite material. As the hydrothermal time is extended to 3 hours, the zirconium oxide crystals grow moderately and are evenly distributed, the reduction degree of RGO is better, the structure of the material is more stable and the electromagnetic loss capacity is improved, thereby significantly enhancing the wave absorption performance. However, too long hydrothermal time (5 hours) leads to excessive growth and agglomeration of zirconium oxide particles. The excessive reduction of RGO may weaken its bonding with zirconium oxide, resulting in a decrease in the electromagnetic loss capacity of the composite material and a weakening of the wave absorption performance. Therefore, when the hydrothermal time is 3 hours, the wave absorption performance of the composite material is the best, and the interaction between zirconium oxide particles and RGO is the most effective.
[0102] Hydrothermal temperature comparison experiment:
[0103] Comparative Example 5
[0104] A method for preparing a reduced graphene oxide@zirconia absorbing composite material using a hydrothermal technique is carried out according to the following steps:
[0105] S1 Take RGO and Zr(NO3)4·5H2O with a molar mass ratio of 1:0.2, mix them with 40mL of deionized water, stir the mixed solution ultrasonically for 1 hour, and stir the dispersed solution magnetically for 0.5 hour to make RGO and Zr(NO3)4·5H2O uniformly dispersed in the solution.
[0106] S2 Take a certain amount of NH3·H2O and add NH3·H2O dropwise to the reaction mixture to adjust the pH value to 9.
[0107] S3 transferred the dissolved solution into a 100 mL stainless steel high-pressure reactor, the reaction temperature was 150°C, and the reaction time was 3 hours.
[0108] S4: washing the obtained product with deionized water for a certain number of times to make the pH value reach a neutral value.
[0109] After washing, S5 was dried in a vacuum oven at 60 °C for 24 h.
[0110] S6 puts the product into an atmosphere furnace for calcination at 400°C for 3 hours, and performs a performance test on the final product.
[0111] Comparative Example 6
[0112] A method for preparing a reduced graphene oxide@zirconia absorbing composite material using a hydrothermal technique is carried out according to the following steps:
[0113] S1 Take RGO and Zr(NO3)4·5H2O with a molar mass ratio of 1:0.2, mix them with 40mL of deionized water, stir the mixed solution ultrasonically for 1 hour, and stir the dispersed solution magnetically for 0.5 hour to make RGO and Zr(NO3)4·5H2O uniformly dispersed in the solution.
[0114] S2 Take a certain amount of NH3·H2O and add NH3·H2O dropwise to the reaction mixture to adjust the pH value to 9.
[0115] S3 transferred the dissolved solution into a 100 mL stainless steel high-pressure reactor, the reaction temperature was 210 ° C, and the reaction time was 3 hours.
[0116] S4: washing the obtained product with deionized water for a certain number of times to make the pH value reach a neutral value.
[0117] After washing, S5 was dried in a vacuum oven at 60 °C for 24 h.
[0118] S6 puts the product into an atmosphere furnace for calcination at 400°C for 3 hours, and performs a performance test on the final product.
[0119] Analysis of hydrothermal temperature principle:
[0120] The hydrothermal temperature has a significant effect on the wave absorption performance of reduced graphene oxide composite zirconium oxide (RGO@ZrO2) materials. The experimental results show that when the hydrothermal temperature is 180℃, the zirconium oxide crystals can grow uniformly, the particle size is moderate and the distribution is uniform, and the reduction effect of RGO can be fully exerted, thus forming a stable composite structure, which significantly improves the electromagnetic loss capacity and wave absorption performance of the material. At a lower temperature (150℃), the zirconium oxide crystals grow slowly, the particles are small and unevenly distributed, and the reduction degree of RGO is insufficient, resulting in poor wave absorption performance of the composite material; at a higher temperature (210℃), the zirconium oxide particles grow excessively and may agglomerate, and the excessive reduction of RGO may also damage its surface functional groups, thereby affecting the combination of the two and the wave absorption effect of the composite material. Therefore, a hydrothermal temperature of 180℃ is the optimal condition for preparing RGO@ZrO2 composite materials with the best wave absorption performance.
[0121] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.
[0122] Compared with the existing atomic layer deposition technology to prepare graphene@alumina composite materials:
[0123] Comparative Example 7
[0124] In a method for preparing a graphene@alumina absorbing composite material using atomic layer deposition technology, graphene is used as a base material and alumina is used as a deposition material. Through atomic layer deposition and other technologies, a graphene@alumina composite material with excellent absorbing performance in a high temperature environment is finally obtained.
[0125] ① Take 16 mg of graphene, mix it with 40 mL of ethanol, and stir the mixed solution ultrasonically for 0.5-2 hours to evenly disperse the graphene in the ethanol solution.
[0126] ② Evenly drop the dispersed mixed solution onto the quartz wafer, and then let it stand for 1-2 hours to allow the ethanol to evaporate.
[0127] ③ Place graphene in a closed hot-wall atomic layer deposition reactor. The graphene in the reactor is exposed to trimethylaluminum and water to deposit an aluminum oxide coating. The temperature of the precursor is maintained at 60°C-80°C, and the substrate temperature is 180°C-200°C during deposition.
[0128] ④ The thickness of alumina covering graphene is controlled by controlling the number of cycles of depositing alumina. The number of cycles is generally 100-300 times. After atomic layer deposition, samples are collected, marked, and performance tested.
[0129] The measured absorbing properties are worse than the performance of the reduced graphene oxide@zirconia absorbing composite material prepared by hydrothermal technology in this patent.
[0130] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.
Claims
1. A method for preparing reduced graphene oxide @ zirconium oxide wave absorbing composite material by hydrothermal technology, characterized in that: The method comprises the following preparation steps: S1 was fully fused with Zr(NO3)4·5H2O and RGO in deionized water, and the mixed solution was magnetically stirred; S2 added NH3·H2O to adjust the pH value; S3 reacts the mixed solution in a stainless steel high-pressure reactor; S4 washing the product; S5 dries the product; After S6 drying, the obtained product is calcined in an atmosphere furnace.
2. The method for preparing reduced graphene oxide@zirconia absorbing composite material by hydrothermal technology according to claim 1, characterized in that: The detailed steps of S1 are: RGO and Zr(NO3)4·5H2O with molar mass ratios of 1:0.1, 1:0.2, and 1:0.3 were taken respectively, mixed with 40 mL of deionized water, the mixed solution was ultrasonically stirred for 0.5-2 hours, and the dispersed solution was magnetically stirred for 0.5-2 hours to uniformly disperse RGO and Zr(NO3)4·5H2O in the solution.
3. The method for preparing reduced graphene oxide@zirconia absorbing composite material by hydrothermal technology according to claim 1, characterized in that: The detailed steps of S2 are as follows: taking 0.5 mL of NH3·H2O, adding NH3·H2O dropwise to the reaction mixture, and adjusting the pH value to 9.
4. The method for preparing reduced graphene oxide@zirconia absorbing composite material by hydrothermal technology according to claim 1, characterized in that: The detailed steps of S3 are: transferring the dissolved solution into a 100 mL stainless steel high-pressure reactor, the reaction temperature is 150° C.-210° C., and the reaction time is 1-5 hours.
5. The method for preparing reduced graphene oxide@zirconia absorbing composite material by hydrothermal technology according to claim 1, characterized in that: The detailed steps of S4 are: washing the obtained product with deionized water to make the pH value reach a neutral value.
6. The method for preparing reduced graphene oxide@zirconia microwave absorbing composite material by hydrothermal technology according to claim 1, characterized in that: The detailed steps of S5 are: after washing, drying in a vacuum oven at 60° C. for 24 hours.
7. The method for preparing reduced graphene oxide@zirconia absorbing composite material by hydrothermal technology according to claim 1, characterized in that: The detailed steps of S6 are: placing the product in an atmosphere furnace for calcining at 400° C. for 3 hours to obtain a final product.